Hollow Spherical Pd/CdS/NiS with Carrier Spatial Separation for Photocatalytic Hydrogen Generation - Xiao Wang; Fei Zhao; Nan Zhang; Wenli Wu; Yuhua Wang (Nanomaterials, 2023)
Inspired by the unique properties of the three-dimensional hollow nanostructures in the field of photocatalysis, as well as the combination of co-catalyst, porous hollow spherical Pd/CdS/NiS photocatalysts are prepared by stepwise synthesis. The results show that the Schottky junction between Pd and CdS accelerates the transport of photogenerated electrons, while a p-n junction between NiS and CdS traps the photogenerated holes. As co-catalysts, the Pd nanoparticles and the NiS are loaded inside and outside the hollow CdS shell layer, respectively, which combines with the particular characteristic of the hollow structure, resulting in a spatial carrier separation effect. Under the synergy of the dual co-catalyst loading and hollow structure, the Pd/CdS/NiS has favorable stability. Its H2 production under visible light is significantly increased to 3804.6 μmol/g/h, representing 33.4 times more than that of pure CdS. The apparent quantum efficiency is 0.24% at 420 nm. A feasible bridge for the development of efficient photocatalysts is offered by this work.